Strengthening the Nagari Koto Tangah Islamic Study Group in Tilkam Subdistrict, Agama Regency, Through Training on Funeral Arrangements - Gazali Gazali; Yelfi Dewi S (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2026)
The handling of the deceased is one of the obligatory acts of worship classified as a fardhu kifayah. Not all Muslims possess the skills to wash, shroud, and perform the funeral prayer for the deceased; typically, these duties are entrusted to those who are experts and accustomed to performing them. However, it is also important for every Muslim to know and understand these religious laws, at least for the purpose of handling the funeral of close relatives. To provide insight to those who have not yet mastered this knowledge, a training session was conducted involving the Majelis Taklim in Kanagarian Koto Tangah, Tilatang Kamang Subdistrict, Agam Regency. This was done in anticipation of a shortage of funeral organizers in the area. Several studies indicate that community service programs based on Majelis Taklim, focusing on funeral arrangements, remain limited. This initiative aims to enrich existing efforts while addressing a different subject area. The methodology employs a Participatory Action Research approach, utilizing lectures and demonstrations. In this community service project, two major patterns were identified: the importance of strengthening literacy and the need for demonstrations aimed at fostering habitual practices in a religious activity that is often performed on an ad hoc basis. The training on funeral arrangements for the Majelis Taklim in Koto Tangah Village has resulted in a task force that is on standby at all times to provide services to families experiencing bereavement